Impacts of Reducing Food Losses Across the Value Chain - Vos, Rob (2019)
IFPRI's Director of Markets, Trade and Institutions Division (MTID), Rob Vos discussed findings from IFPRI's study and explains the complexity of measuring food loss, and identifying its causes and consequences.